Linguistic errors in school textbooks – examples from the primary school reading textbook - hammou, naima (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : Texts are considered as means for learning the Arabic language in which we derive examples to teach Arabic grammatical rules, it is known as the textual approach, that's why it is highly recommended to develop it without making grammatical mistakes at the level of expression and the communication in its both aspects the verbal and the written one . Our study aims at exploring the educational sources embodied in the educational materials in the texts books of the second generation of the primary school represented by 3rd year and 4rt year, including the curriculum. This paper will attempt to answer the following question: Do the texts used for these levels represent really the textual approach ?